Jet fuel price variations and market value: a focus on low-cost and regular airline companies - Gaudenzi, Barbara; Bucciol, Alessandro (Journal of Business Economics and Management, 2016)
We analyze the relationship between dynamics to stock prices and jet fuel prices, conditional on financial and company-specific variables, in the airline sector. In particular, our contribution to the literature is in the comparison between regular and low-cost airline companies. We run a set of fixed-effect regressions where the dependent variable, the stock daily return of the airline company (observed between 2008 and 2014) is regressed over three sets of explanatory variables (financial, company-specific and time variables). While large and small companies provide similar results, we find that the company price return – among different variables – correlates only with the jet fuel return and the stock market return. Our work also suggests that there is a difference between regular and low-cost companies. We speculate that this possibly arises because low-cost companies stock-pile in a more efficient way, which depends less on current jet fuel price. Our evidence then sheds light on the efficiency of the low-cost model and may suggest to export part of its practice among regular airline companies.